EPIDEMIOLOGY, TREATMENT, AND COMPLICATIONS OF CROUP SYNDROME IN CHILDREN - Gjinovska Tasevska, Elena; Doksimovski, Filip; Boskovska, Katerina; Tasevska Rajkovikj, Аna; Petlichkovska, Sandra; Jakjovska, Tatjana; Arnaudova Danevska, Ivana (Macedonian Association of Anatomists and Morphologists, 2020)
Introduction: Croup syndrome is an urgent pediatric condition. It is characterized by the abrupt onset, most commonly at night, of a barking cough, that is usually accompanied by inspiratory stridor, hoarseness and respiratory distress resulting from upper-airway obstruction. This is the most common reason why parents are upset and immediately seek medical help. Objective: This study aimed to evaluate the frequency, treatment, and possible complications of croup syndrome in children hospitalized at our institute. Materials and methods: In our retrospective study we examined 56 pediatric cases with croup syndrome that were hospitalized in our Institute and we analyzed gender and age, the season in which we had the most frequent hospitalizations of children with croup syndrome, as well as treatment and possible complications after completion of croup symptoms. Period of examination was one year. Results: Mean age at diagnosis of children with croup was 26,5 ±2.6 months (range from 45 days to 8 years). As well the world statistics we got a larger number of hospitalized boys with croup syndrome, rather than girls (ratio 2,3:1). Regarding the period of the year, the autumn period was dominant. As far as the treatment, we noticed significant number of children with moderate to severe croup syndrome that required in-patient care. All of them received nebulized adrenalin as well as parenteral corticosteroid. The average duration of the hospitalizations that occurred in our unit for close monitoring and semi-intensive care was 5 days (1-14d). Antibiotics were used in 71% (n=40). Most common comorbidity was pneumonia and bronchopneumonia (14,2%, n=8). None of the children was of need of intubation and referral to intensive care unit. Conclusion: Our one-year research has documented considerable number of children with the necessary hospitalization, as many as 10% of hospitalized children in our Institute were due to moderate to severe croup syndrome. The sex, the age of the children as well as the season are most often in line with world statistics. We are noticing high percent of hospitalized patients with moderate croup. There is evident discrepancy between the use of antibiotics and its duration in our practice in comparison with other reports. These observations lead to reassessment of the hospitalization criteria as well as more rational use of antibiotics.
Keywords: Croup syndrome; intensive care; pediatric; treatment